THE EFFECTIVENESS OF SPEED READING TECHNIQUE TOWARDS STUDENT' READING COMPREHENTION IN FABLE TEXTS - Nugroho, Endy Pandu (Academy of Education Journal, 2023)
The purpose of the study is to know the effectiveness of speed reading technique toward students’ reading comprehension in fable text. A researcher discovered numerous reading errors made by students. True experimental research was used in the design of this study. Students from the experimental group and students from the control group were divided into Effective Reading Rate (ERR) groups for the pre-test and post-test. Students in the experimental group improve their effective reading rate at a faster rate than students in the control group. In the post-test, 2 of the experimental group's students (20%) and 8 of the experimental group's pupils (80%) were categorised as above average readers. 10 kids (100%) in the control group were identified as talkers. The researcher draws the conclusion that the use of speed reading techniques can help students understand fable texts better based on the results.